Optical Coherence Tomography to Assess Neurodegeneration in Phenylalanine Hydroxylase Deficiency - Lotz-Havla, Amelie S.; Weiß, Katharina; Schiergens, Katharina; Regenauer-Vandewiele, Stephanie; Parhofer, Klaus G.; Christmann, Tara; Böhm, Luise; Havla, Joachim; Maier, Esther M. (Frontiers in Neurology, 2021)
In phenylalanine hydroxylase (PAH) deficiency an easily feasible method to access progression of neurodegeneration is warranted to contribute to current discussions on treatment indications and targets. The objective of the present study was to investigate whether optical coherence tomography (OCT) measures as markers of neurodegeneration differ between patients with PAH deficiency and healthy controls (HC) according to phenotype and metabolic control. In this single-center cross-sectional study, 92 patients with different phenotypes of PAH deficiency (PAH deficiency not requiring treatment, early treated phenylketonuria (ETPKU) and late-diagnosed phenylketonuria) compared to 76 HC were examined using spectral-domain OCT. Indices of phenylalanine elevation and variability were correlated with OCT parameters. Late-diagnosed PKU patients showed reduced peripapillary retinal nerve fiber layer thickness (pRNFL) and combined ganglion cell and inner plexiform layer volume (GCIPL). Adult ETPKU patients were found to have lower GCIPL atrophy volume (p = 0.016), which correlated with indices of phenylalanine control. In pediatric ETPKU patients with poor metabolic control, pRNFL was significantly reduced (p = 0.004). PAH deficient patients not requiring treatment did not exhibit retinal degeneration. Inner nuclear layer (INL) was significantly increased in pediatric ETPKU patients, driven by those with current poor metabolic control (p = 0.006). Our data provide evidence of retinal neuroaxonal degeneration and INL swelling, depending on phenotype, current age, and metabolic control. These findings suggest that OCT is suitable to investigate neurodegeneration in PKU and we propose OCT as a sensitive, reliable, safe, low-burden, and low-cost examination for future multicenter studies.